Interleukin-6 inhibition in the treatment of autoinflammatory diseases - Koga, Tomohiro; Kawakami, Atsushi (Frontiers in Immunology, 2022)
Autoinflammatory diseases are characterized by abnormalities that prevent innate immune cells from producing autoantibodies. While interleukin (IL)-6 is not directly associated with inflammasomes, like IL-1β or IL-18, it plays an important role in the pathogenesis of autoinflammatory diseases. Studies of autoinflammatory diseases, such as familial Mediterranean fever, cryopyrin-associated periodic syndrome, and tumor necrosis factor receptor-associated periodic syndrome, have shown IL-6 to be a promising therapeutic target. It has also been suggested that inhibition of IL-6 may have a therapeutic effect on amyloidosis, which is frequently associated with these chronic inflammatory diseases. In this study, we discuss the most recent research on the role of IL-6 in autoinflammatory diseases and its potential as a therapeutic target in their treatment.